Current state of balance assessment during transferring, sitting, standing and walking activities for the spinal cord injured population: A systematic review. (2nd January 2020) - Arora, Tarun; Oates, Alison; Lynd, Kaylea; Musselman, Kristin E.
Abstract : Context: Comprehensive balance measures with high clinical utility and sound psychometric properties are needed to inform the rehabilitation of individuals with spinal cord injury (SCI). Objective: To identify the balance measures used in the SCI population, and to evaluate their clinical utility, psychometric properties and comprehensiveness. Methods: Medline, PubMed, Embase, Scopus, Web of Science, and the Allied and Complementary Medicine Database were searched from the earliest record to October 19/16. Two researchers independently screened abstracts for articles including a balance measure and adults with SCI. Extracted data included participant characteristics and descriptions of balance measures. Quality was evaluated by considering study design, sampling method and adequacy of description of research participants. Clinical utility of all balance measures was evaluated. Comprehensiveness was evaluated using the modified Systems Framework for Postural Control. Results: 2820 abstracts were returned and 127 articles included. Thirty-one balance measures were identified; 11 evaluated a biomechanical construct and 20 were balance scales. All balance scales had high clinical utility. The Berg Balance Scale and Functional Reach Test were valid and reliable, while the mini-BESTest was the most comprehensive. Conclusion: No single measure had high clinical utility, strong psychometric properties and comprehensiveness. The mini-BESTest and/or Activity-based Balance Level Evaluation may fill this gap with further testing of their psychometric properties.